If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + g = 16 Solving 12 + g = 16 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + g = 16 + -12 Combine like terms: 12 + -12 = 0 0 + g = 16 + -12 g = 16 + -12 Combine like terms: 16 + -12 = 4 g = 4 Simplifying g = 4
| t+15=19 | | sqrt(3x+2)=xsqrt(2) | | 12=((-3+1)(-3+1))(k) | | =x^4-6x^3+13*x^2-12*x+5 | | 0.5x(x-3)=54 | | x=2(6+2x)+8x | | 8x-20=2x-8 | | A=5*5*5(3.5) | | w+3/4=6 | | 3x+2=x^2-2 | | px^2-6x+p=0 | | 2x-36+x=90 | | 3x=2+5 | | 3j-9=6 | | 4x^2y-6xy^2=u | | 3x+x+2+4=18 | | x^2+x^2=c | | 9m-9=-45 | | x^2*X^2=c^2 | | C=(3C+5)+(4C-8) | | 12-x=4(x+13) | | 2(7x+1)=3(x+8) | | 4(x+1)=8(8-x) | | 9x-5=8x-0 | | 93-49= | | 5(y+-3)=20 | | 6d=(12-6) | | ln(500+x)=0 | | 4(m+6)-3(2m+1)=2(4m+7)+17 | | log(5+4x)+2logx=0 | | 4x-3=4x-43 | | 3(9-y)=5(y-9) |